APLIKASI METODE QUALITY FUNCTION DEPLOYMENT (QFD) UNTUK PENINGKATAN KUALITAS PRODUK MIE JAGUNG - Ida Bagus Suryaningrat; . Djumarti; Eka Ruriani; Indah Kurniawati (JURNAL AGROTEKNOLOGI, 2010)
As a new product, the information of customer satisfaction was strongly needed by corn noodle product for quality improvement. This research objective were to identify customer expectations, product attributes and customer satisfaction to the corn noodle, and to develop a strategy for product improvement. Questionnaire was addressed to customers for data collection which was analyzed using Quality Function Deployment (QFD) method. The result could be seen from house of quality as a situation of customer expectation. The result showed that based on the customer satisfaction level, from 4 attributes such as taste, elasticity, color and texture, only taste could be reached by corn noodle product. In targeting aspect, found that corn noodle could meet the target of technical response such as quantity of egg and salt. Other technical responses such as quantity reduction of wheat flour to keep the taste and additional quantity of corn flour to keep the noodle’ color, still could not be reached by corn noodle. The strategy of product improvement is detailed in this paper.Keywords: mie jagung, mutu produk, Quality Function Deployment (QFD)